2016
DOI: 10.1016/j.jesf.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Policy, environment, and worksite fitness program participation among financial enterprise employees in Taiwan

Abstract: Background/ObjectiveThis study explored the intertwined effects between the policies and regulations of the companies and personal background on participation in the physical fitness programs and leisure-time activities in financial enterprises.MethodsA total of 823 employees were selected as the sample with the multilevel stratification random-sampling technique. The response rate was 52.0%. Data were analyzed with descriptive statistics and hierarchical linear logistic regression.ResultsThirty-two percent an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Although the staff of government agencies and public institutions spend 1/3 of their day on sedentary work, the work unit could actively carry out the sports activities and encourage people to participate in sports competitions. To pass the national physical fitness test, some institutions not only implemented national fitness education but also provided a suitable environment to promote employees exercising ( 60 ). Farmers tended to do LPA, such as repeatedly standing upright and bending the waist to harvest crops.…”
Section: Discussionmentioning
confidence: 99%
“…Although the staff of government agencies and public institutions spend 1/3 of their day on sedentary work, the work unit could actively carry out the sports activities and encourage people to participate in sports competitions. To pass the national physical fitness test, some institutions not only implemented national fitness education but also provided a suitable environment to promote employees exercising ( 60 ). Farmers tended to do LPA, such as repeatedly standing upright and bending the waist to harvest crops.…”
Section: Discussionmentioning
confidence: 99%
“…Employed adults spend at least one-third of their day at work; thus, the work environment can be shaped to promote healthier behavior among employees and to improve their lifestyles (Kent et al, 2016). A previous Asian study (Huang & Hung, 2016) demonstrated the workplace to be an ideal avenue for delivering initiatives to promote physical activity. For example, establishing fitness centers not only encouraged the participation of employees not previously involved in physical activity but also effectively strengthened the motivation of those already participating in physical activities.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have identified the mobile platform as an effective means for promoting physical activity behavior (Huang & Hung, 2016; Rayward et al, 2018). Short Message Service (SMS, that is, texting), as an intervention tool, presents the advantages of low cost, no spatial or temporal limitations, and a high subscription rate, and it has been demonstrated to be effective in increasing physical activity in school children (Lau et al, 2015) and postnatal women (Fjeldsoe et al, 2010).…”
Section: Introductionmentioning
confidence: 99%